2013
DOI: 10.7567/jjap.52.042401
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Complex Refractive Index with Standard Deviation of ZnTe Measured by Terahertz Time Domain Spectroscopy

Abstract: Accurate complex refractive index of ZnTe crystal in terahertz spectral region from 0.2 to 3.5 THz is obtained by measuring three samples with different thickness using transmission terahertz time-domain spectroscopy. Each sample is measured a number of times and the mean and standard deviation (SD) of the complex refractive index are calculated to quantify the random errors in the measurement. The ratios of SD to mean of the real and imaginary parts of the refractive index are approximately 1.0×10-4 and 1.2×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 24 publications
(32 reference statements)
2
2
0
Order By: Relevance
“…Static THz-TDS measurements revealed that the THz transmission magnitude was nearly equivalent to a measurement of dry purged air (implying zero THz absorption when corrected for surface reflections in the THz spectral range 0.3 THz to 2.1 THz according to the index of refraction and Fresnel equation) for all the samples except ZnTe. For the ZnTe sample studied, the THz transmission was significantly attenuated and yielded a peak THz absorption at 1.7 THz, in agreement with other THz absorption measurements [41]. This THz-TDS absorption in ZnTe is not likely the result of free charge carriers but a low energy phonon absorption in the THz range (there are two weak absorptions < 2 THz, but the strong optical phonon band is centered at 5 THz).…”
Section: Resultssupporting
confidence: 87%
“…Static THz-TDS measurements revealed that the THz transmission magnitude was nearly equivalent to a measurement of dry purged air (implying zero THz absorption when corrected for surface reflections in the THz spectral range 0.3 THz to 2.1 THz according to the index of refraction and Fresnel equation) for all the samples except ZnTe. For the ZnTe sample studied, the THz transmission was significantly attenuated and yielded a peak THz absorption at 1.7 THz, in agreement with other THz absorption measurements [41]. This THz-TDS absorption in ZnTe is not likely the result of free charge carriers but a low energy phonon absorption in the THz range (there are two weak absorptions < 2 THz, but the strong optical phonon band is centered at 5 THz).…”
Section: Resultssupporting
confidence: 87%
“…For evaluating a(Ω) and β 1 (Ω), we measure the complex refractive indices of the two EO crystals in the terahertz frequency range and the group velocities of the probe pulse inside the EO crystals. The obtained values of the complex refractive indices and the group velocities for the two EO crystals are similar to those reported in previous works [14,104,105]. Since χ (2) is proportional to r 41 , we used the values r 41 = 4 pm/V for ZnTe and r 41 = 1 pm/V for GaP [14].…”
Section: Retrieval Of the Elliptically-polarized Terahertz Time-domaisupporting
confidence: 74%
“…From the terahertz time-domain electric-field waveforms obtained with and without sample, it is possible to calculate the complex refractive index spectrum N ̂(ω) = n(ω) + ik(ω) of the sample as a function of the optical angular frequency, ω. 42 The complex dielectric constant that is defined as ε(ω) = ε′(ω) + iε″(ω) 43 can be calculated from N ̂(ω) by using the relation ε(ω) = {N ̂(ω)} 2 . Figure 2 shows the real (ε′) and imaginary parts (ε″) of the dielectric functions of the 16 PLA films in the terahertz frequency range measured by our THz-TDS system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%